FEM Analysis of Innovative Shallow Foundation System for Reactive Soils - Ismail, M.; Shahin, Mohamed (The GEOMATE Internatinal Society, 2011)
Granular pile anchor foundations (GPAF) are a promising foundation system that can be used to mitigate the serious consequences of volumetric changes of reactive soils, both during expansion and shrinkage. This paper presents results from 3D finite element analyses, using PLAXIS software, undertaken on a typical double-story building constructed over a system of GPAF in a reactive soil. The study investigates the ability of the GPAF system to resist the forces induced by soil movement due to moisture variation, and the impact of this resistance on the straining actions affecting the superstructure. The results confirm the efficiency of the GPAF system in arresting the movement of the reactive soil, which in turn improves the structural responses of the building in terms of induced deformations, angular distortions and internal forces.